Targeting insulin inhibition as a metabolic therapy in advanced cancer: A pilot safety and feasibility dietary trial in 10 patients - Fine, Eugene J.; Segal-Isaacson, C.J.; Feinman, Richard D.; Herszkopf, Silvia; Romano, Maria C.; Tomuta, Norica; Bontempo, Amanda F.; Negassa, Abdissa; Sparano, Joseph A. (Nutrition (Burbank, Los Angeles County, Calif.), 2012)
Most aggressive cancers demonstrate a positive positron emission tomographic (PET) result using 18F-2-fluoro-2-deoxyglucose (FDG), reflecting a glycolytic phenotype. Inhibiting insulin secretion provides a method, consistent with published mechanisms, for limiting cancer growth. Eligible patients with advanced incurable cancers had a positive PET result, an Eastern Cooperative Oncology Group performance status of 0 to 2, normal organ function without diabetes or recent weight loss, and a body mass index of at least 20 kg/m2. Insulin inhibition, effected by a supervised carbohydrate dietary restriction (5% of total kilocalories), was monitored for macronutrient intake, body weight, serum electrolytes, β-hydroxybutyrate, insulin, and insulin-like growth factors-1 and -2. An FDG-PET scan was obtained at study entry and exit. Ten subjects completed 26 to 28 d of the study diet without associated unsafe adverse effects. Mean caloric intake decreased 35 ± 6% versus baseline, and weight decreased by a median of 4% (range 0.0–6.1%). In nine patients with prior rapid disease progression, five with stable disease or partial remission on PET scan after the diet exhibited a three-fold higher dietary ketosis than those with continued progressive disease (n = 4, P = 0.018). Caloric intake (P = 0.65) and weight loss (P = 0.45) did not differ in those with stable disease or partial remission versus progressive disease. Ketosis was associated inversely with serum insulin levels (P = 0.03). Preliminary data demonstrate that an insulin-inhibiting diet is safe and feasible in selected patients with advanced cancer. The extent of ketosis, but not calorie deficit or weight loss, correlated with stable disease or partial remission. Further study is needed to assess insulin inhibition as complementary to standard cytotoxic and endocrine therapies.